Moonlight screenplay book - Jenkins, Barry 1979-; McCraney, Tarell Alvin 1980- (A24 Films LLC, 2020)
« Starting with Ex Machina by Alex Garland, The Witch by Robert Eggers, and Moonlight by Barry Jenkins, the first collection from A24 BOOKS celebrates the singular vision and unbridled artistry of these noted writer-directors, showcasing how they saw their films through from script to screen. »--
« Run time : 115 min » -- Cover
Keywords: Moonlight; Moonlight (Motion picture : 2016); Motion picture authorship; Motion picture plays; African American men / Fiction; African American families / Fiction; Moonlight (Film); Cinéma / Art d'écrire; Scénarios de cinéma; Hommes noirs américains / Romans, nouvelles, etc; Familles noires américaines / Romans, nouvelles, etc; screenplays; Screenplays; Drehbuch; Hochschulschrift